Implementasi Program Pendidikan Inklusi Melalui Program Pembelajaran Individual (PPI) Bagi Siswa ABK di SD - Putri Natasya Azzahra; Ahmad Suriansyah; Arta Mulya Budi Harsono (CV. ITTC INDONESIA, 2025)
This research is motivated by the importance of inclusive education to provide equal opportunities for students with special needs (ABK) to learn alongside regular students. The purpose of this study is to examine in more depth the implementation of the inclusive education program through the adjustment of the Individual Learning Program (PPI) in inclusive elementary schools, and to examine how the collaboration between class teachers and GPK influences this process. This research method uses a qualitative case study design approach with data obtained through observation, interviews, and documentation to obtain information about the case discussed in this study. This research was conducted at an elementary school that provides inclusive education in Banjarmasin City, namely SDN Kebun Bunga 1. Data analysis was carried out in three stages starting from data reduction, data presentation, and drawing conclusions. The results of the study indicate that PPI is implemented through adjustments to learning objectives, learning strategies, and development evaluations for students with special needs that have been adjusted to their needs. Collaboration between class teachers and GPK in developing the PPI is a factor in the successful implementation of inclusive education. Overall, the adjustment of PPI in the inclusive education program plays a crucial role in ensuring the effectiveness of inclusive education in elementary schools.